Regional Clustering of Indonesia's Manufacturing Industry:A Spatial Analysis with Gegraphic Information System(GIS) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Abimanyu, A. 1996. The Indonesian economy and total factor productivity. Anselin, L., and R.J.G.M. Florax (Eds.). 1995. New Directions in Spatial Econometrics. Aziz, I.J. 1994. Ilmu Ekonomi Regional dan Beberapa Aplikasinya di Indonesia (Regional Economics and Its Some Applications in Indonesia Barlow, C., and T.K. Wie. 1989. North Sumatra: Growth with unbalanced development..